Revisiting the dystrophin-ATP connection: How half a century of research still implicates mitochondrial dysfunction in Duchenne Muscular Dystrophy aetiology. Issue 6 (December 2015) - Timpani, Cara A.; Hayes, Alan; Rybalka, Emma
Abstract: Duchenne Muscular Dystrophy (DMD) is a fatal neuromuscular disease that is characterised by dystrophin-deficiency and chronic Ca 2+ -induced skeletal muscle wasting, which currently has no cure. DMD was once considered predominantly as a metabolic disease due to the myriad of metabolic insufficiencies evident in the musculature, however this aspect of the disease has been extensively ignored since the discovery of dystrophin. The collective historical and contemporary literature documenting these metabolic nuances has culminated in a series of studies that importantly demonstrate that metabolic dysfunction exists independent of dystrophin expression and a mild disease phenotype can be expressed even in the complete absence of dystrophin expression. Targeting and supporting metabolic pathways with anaplerotic and other energy-enhancing supplements has also shown therapeutic value. We explore the hypothesis that DMD is characterised by a systemic mitochondrial impairment that is central to disease aetiology rather than a secondary pathophysiological consequence of dystrophin-deficiency.